The ultimate dinosaur book - Lambert, David (London Dorling Kindersley, 1993)
This volume contains models and pictorial profiles of all the best-known and best preserved specimens of dinosaurs. It covers all aspects of dinosaurs' lives and uncovers new research which should provide a more complete and up-to-date understanding of dinosaurs than before.